Medicinal Plants Used by Various Tribes of Bangladesh for Treatment of Malaria. (23rd January 2012) - Rahmatullah, Mohammed; Hossan, Shahadat; Khatun, Afsana; Seraj, Syeda; Jahan, Rownak
Abstract : It has been estimated that 300–500 million malaria infections occur on an annual basis and causes fatality to millions of human beings. Most of the drugs used for treatment of malaria have developed drug-resistant parasites or have serious side effects. Plant kingdom has throughout the centuries proved to be efficient source of efficacious malarial drugs like quinine and artemisinin. Since these drugs have already developed or in the process of developing drug resistance, it is important to continuously search the plant kingdom for more effective antimalarial drugs. In this aspect, the medicinal practices of indigenous communities can play a major role in identification of antimalarial plants. Bangladesh has a number of indigenous communities or tribes, who because of their living within or in close proximity to mosquito-infested forest regions, have high incidences of malaria. Over the centuries, the tribal medicinal practitioners have treated malaria with various plant-based formulations. The objective of the present study was to conduct an ethnomedicinal survey among various tribes of Bangladesh to identify the plants that they use for treatment of the disease. Surveys were conducted among seven tribes, namely, Bawm, Chak, Chakma, Garo, Marma, Murong, and Tripura, who inhabit the southeastern or northcentral forested regions of Bangladesh. Interviews conducted with the various tribal medicinal practitioners indicated that a total of eleven plants distributed into 10 families were used for treatment of malaria and accompanying symptoms like fever, anemia, ache, vomiting, and chills. Leaves constituted 35.7% of total uses followed by roots at 21.4%. Other plant parts used for treatment included barks, seeds, fruits, and flowers. A review of the published scientific literature showed that a number of plants used by the tribal medicinal practitioners have been scientifically validated in their uses. Taken together, the plants merit further scientific research towards possible discovery of novel compounds that can be used to successfully treat malaria with less undesirable sideeffects.